Valvular involvement in ANCA-associated systemic vasculitis: a case report and literature review - Cohen Pascal (BMC Musculoskeletal Disorders, 2011)
Abstract Background Antineutrophil cytoplasmic antibodies (ANCA)-associated systemic vasculitides have a variety of presentations, but cardiac valvular involvement is rarely diagnosed and its management is not established. Case presentation We report the case of a 44 year old man who presented with an ANCA-associated systemic vasculitis and aortic regurgitation of unusual mechanism. Transthoracic and transesophageal echocardiography disclosed septal hypertrophy preventing a complete closure of the aortic valve and thus responsible for a massive aortic regurgitation. After 4 months of immunosuppressive therapy, the valve lesion did not subside and the patient had to undergo aortic valve replacement. This report also reviews the 20 cases of systemic ANCA-associated vasculitis with endocardial valvular involvement previously reported in the English language medical literature. Conclusions Valvular involvement in ANCA-associated systemic vasculitides is rarely reported. Most of these lesions are due to Wegener's granulomatosis and half are present when the diagnosis of vasculitis is made. The valvular lesion is usually isolated, aortic regurgitation being the most frequent type, and often requires valve replacement in the months that follow it's discovery.